Variation in sepsis care: a wake-up call - Hartman, Mary E (BioMed Central, 2003)
There is important variation in the care of critically ill patients. While some of this variability is appropriate, and represents individually titrated care, residual variation indicates over- and under-use of precious resources and is clearly concerning. Recent advances in critical care medicine provide "road maps" to standardize care and use evidence-based medicine to improve patient outcomes. Knowledge about which therapies to use, and under what circumstances to use them, could form a basis for measuring the consistency and quality of our care processes. These simple process measures can be easily incorporated into daily rounds and serve to inform on the quality of our care.